2017
DOI: 10.12691/ajfst-5-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Anthocyanins in Butterfly Pea (<i>Clitoria ternatea</i> L.) Flower Extract at pH 7

Abstract: The degradation of anthocyanins from Clitoria ternatea L. flower (CT) extract at pH 7 bottled with 0% and 50% volume of headspace (HS0 and HS50, respectively) were studied at various temperatures (7, 30, 45, 60, 75, 90°C). The extract was stable at 7°C up to 56 days. The effect of the presence of headspace to accelerate the degradation was significance at ≥30°C. The color and chemical degradation were adequately be described by the first order reaction kinetics. However, the degradation at 30°C was faster tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…In short, the anthocyanin of butterfly pea flower extract at pH 4.5 was more stable at 50°C than at 30°C. A similar result had also been reported by a previous study (Marpaung et al, 2017a). The study showed that the anthocyanin in butterfly pea flower extract at pH 7 was less stable at 30°C than at 45°C.…”
Section: Total Anthocyaninsupporting
confidence: 91%
“…In short, the anthocyanin of butterfly pea flower extract at pH 4.5 was more stable at 50°C than at 30°C. A similar result had also been reported by a previous study (Marpaung et al, 2017a). The study showed that the anthocyanin in butterfly pea flower extract at pH 7 was less stable at 30°C than at 45°C.…”
Section: Total Anthocyaninsupporting
confidence: 91%
“…Meanwhile, the respective half-life was 27.99, 16.53, and 9.81 days. This anthocyanin stability was comparable to the spray dried, vacuum dried, and freeze dried butterfly pea flower extract powder [8,9] and much more higher than butterfly pea flower extract at pH 7 [16].…”
Section: Stability Testingmentioning
confidence: 64%
“…CI calculated following the method that specifically developed for butterfly pea flower extract [11] with modification (Equation 1). CI = (Aλmax-A700) + (Aλpeak-A700) + (Aλshoulder-A700) (1) Note: Aλmax is the absorbance at λmax, Aλpeak is the absorbance at λpeak, Aλshoulder is the absorbance at λshoulder.…”
Section: Evaluation Of Color Qualitymentioning
confidence: 99%
“…It is an indirect method for monitoring the anthocyanin degradation (Equation 3). BI = (A420 -A700) / (Aλmax -A700) [11] (3) Note: A420 is the absorbance at 420 nm.…”
Section: Evaluation Of Color Qualitymentioning
confidence: 99%